Izboljšanje stika med cementno malto in kontinuiranimi ogljikovimi vlakni - Ivanič, Andrej (Gradbeni vestnik, 2009)
Among various parameters that influence the properties of the composite, the bond between the cementitious matrix and the fibres is the most important one. This paper investigates the influence of admixtures - silica fume and superplasticizer - on the improvement of the bond strength between bundled carbon filaments and cementitious mortars. An overall microstructural analysis has shown that the addition of silica fume strengthen the interfacial transition zone by both the reduction of its porosity and the consumption of CH crystals. The addition of a superplasticizer increased the workability of fresh mortars but the improvement of the bond strength was not significant. Fibre-bundle pull-out tests were caried out to confirm the effectiveness of the admixtures to improve the bond strength. Based on the resulting load-displacement curves, the combination of silica fume and superplasticizer were found to be the most effective in improving the bond strength of the composite.
Keywords: cementni kompoziti; gradbeni materiali; ogljikova vlakna; trdnost